1980
DOI: 10.1111/j.1476-5381.1980.tb09770.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Morphine and the Opioid‐like Peptides in the Rat Vas Deferens

Abstract: 1 Morphine, methadone, levorphanol, pethidine, etonitazene and related morphine-like alkaloids produced an increase in the electrically-evoked muscular contraction of the rat vas deferens. In contrast, the enkephalins and f-endorphin caused inhibition of the twitching.2 The concentration of fi-endorphin required to inhibit by 50% the muscular twitch was about 50 to 100 times less than that of the enkephalins. 3 Pretreatment of the vasa with morphine antagonized the inhibition of the neuromuscular transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1981
1981
1989
1989

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Indeed, in the rat colon, P-endorphin is about 10 times more potent than morphine and about 3 times as potent as the enkephalins. These results are in decided contrast to the relative ratio of potency of these agents as compared to that of morphine in the guinea-pig ileum, mouse or rat vas deferens (Lord et al, 1977;Wuster, Schulz & Herz, 1979;Huidobro, Huidobro-Toro & Miranda, 1980;.…”
Section: Discussioncontrasting
confidence: 46%
“…Indeed, in the rat colon, P-endorphin is about 10 times more potent than morphine and about 3 times as potent as the enkephalins. These results are in decided contrast to the relative ratio of potency of these agents as compared to that of morphine in the guinea-pig ileum, mouse or rat vas deferens (Lord et al, 1977;Wuster, Schulz & Herz, 1979;Huidobro, Huidobro-Toro & Miranda, 1980;.…”
Section: Discussioncontrasting
confidence: 46%
“…The K, values of naloxone against dynorphin-(1-13) and a-neo-endorphin obtained in the present experiments (see Table 2) were close to that obtained in the guinea-pig ileum with K-receptor agonists. Furthermore, in the guinea-pig oesophagus, morphine acts as a partial agonist, as the drug does in the rat vas deferens (Huidobro, Huidobro-Toro & Miranda, 1980;Ishii, Yamamoto, Muraki & Kato, 1981).…”
Section: Discussionmentioning
confidence: 98%
“…(12) reported that morphine acted as an antagonist on the inhibitory effect of Q-endorphin in the isolated vas deferens from naive rats.…”
Section: Discussionmentioning
confidence: 99%